2009
DOI: 10.1056/nejmoa0900094
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Association Studies of Stroke

Abstract: BACKGROUND-The genes underlying the risk of stroke in the general population remain undetermined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
241
3
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 409 publications
(261 citation statements)
references
References 37 publications
11
241
3
6
Order By: Relevance
“…However, the association of variants on chromosome 9p21.3 with ischemic stroke has not been fully verified. Several studies found a positive association [10,11,12,13,14,15,16], but results have been inconsistent [8,9,17,18,19,20] leading to uncertainty about this relationship [21]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the association of variants on chromosome 9p21.3 with ischemic stroke has not been fully verified. Several studies found a positive association [10,11,12,13,14,15,16], but results have been inconsistent [8,9,17,18,19,20] leading to uncertainty about this relationship [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Since 2010, a total of 5,970 DNA samples have been registered belonging to patients (2,688) and controls (3,282). The mean ages of patients and controls were 64.6 ± 19.3 and 56.9 ± 14.9 years, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Genome-wide association study approaches have been adopted for investigating many complex diseases, such as stroke, and have been effective in identifying new genetic variants associated with the risk of disease. However, for stroke studies, genome-wide association studies have so far been applied principally in European, North American and Japanese populations 3,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to stroke prevalence, about 85% is IS, 9% is ICH, and 4% to 5% is due to SAH (Petrea et al, 2009). Environmental factors, such as hypertension, diabetes mellitus, and cigarette smoking, contribute to the risk of stroke, and several lines of evidence indicate that genetic factors are also involved in the development of stroke (Gil-Núñez, 2007;Grysiewicz et al, 2008;Ikram et al, 2009;Lanktree et al, 2010;Matarin et al, 2007). Several candidate genes for the susceptibility to stroke have been studied.…”
Section: Introductionmentioning
confidence: 99%